IMPLEMENTATION OF PEDAGOGICAL ETHICS IN FUTURE TEACHERS (World Bulletin of Management and Law, 2023)
This article discusses the formation of the pedagogical behavior of future teachers. There are examples of teachers' ethics.
Keywords: professional ethics; pedagogical requirements; axiological skills